Pengaruh Green Marketing dan Green Product terhadap Green Purchase Intention pada Alang Alang Zero Waste Shop - Nagigaluh Loryan Madjidan; Raya Sulistyowati (Jurnal Ecogen, 2022)
Globalization, which is increasing, is a factor in the formation of a single event. This is because an environmental issue exists, whether it is one of environmental protection or environmental degradation. Environmental degradation has been ingrained in society's worldview and has been widely publicized through mass or social media. Community and corporate actors are also attempting to improve their attitude and lifestyle in order to conserve the environment by determining the community's impression of green marketing or green marketing. The goal of this research is to get a comprehensive and simultaneous knowledge of the influence of green marketing methods and green items on green purchase intentions at zero-waste retailers. The method employs a quantitative descriptive approach to ascertain the relationship between the researcher's variables. The population in this study were consumers of Alang-Alang Zero Waste Store in Surabaya within 3 months (January-March 2022) as many as 150 respondents, sending samples back to 108 respondents who were sought using purposive sampling technique. Data analysis technique with multiple linear regression analysis, t test and F test. The results of this study suggest the partial and simultaneous effect of green marketing and green products on green purchase intention in alang-alang zero waste shop.